Health and safety questions and answers a practical approach - Perry, Pat, 1954- (Thomas Telford, 2003)
The body of knowledge on safety at work is constantly growing. Each individual chapter in this practical volume deals with a particular aspect of health and safety to act as a reminder to those in positions of responsibility of their remit under the law.